Design and Development of Educational Modular Mobile Robot Platform - Denis Kotarski; Petar Piljek; Tomislav Šančić (Tehnički Glasnik)
This paper presents the design and experimental validation of a modular educational robot platform. The development of a novel modular unmanned ground vehicle (UGV) platform is based on open-source system architecture featuring carefully considered modules and is specifically tailored for application in STEM education. The proposed platform is comprehensive in terms of motion planning and modelling. Mathematical description of the non-holonomic and holonomic configuration of the robot is given, and a derived model is implemented in a software package in order to perform simulations and experiments. The design process resulted in a 3D printed novel brick-based robot chassis, offering advantages such as low manufacturing costs, easy repair and maintenance, and seamless expandability with additional modules. The proposed modular platform underwent validation across three robot configurations and three different control ecosystems.